2022
DOI: 10.18632/aging.203921
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene AK4P1 promotes pancreatic ductal adenocarcinoma progression through relieving miR-375-mediated YAP1 degradation

Abstract: Pseudogenes have been reported to play oncogenic or tumor-suppressive roles in cancer progression. However, the molecular mechanism of most pseudogenes in pancreatic ductal adenocarcinoma (PDAC) remains unknown. Herein, we characterized a novel pseudogene-miRNA-mRNA network associated with PDAC progression using bioinformatics analysis. After screening by dreamBase and GEPIA, 12 up-regulated and 7 down-regulated differentially expressed pseudogenes (DEPs) were identified. According to survival analysis, only e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…39) The amplification of AK4P1 may promote the development and progression of pancreatic ductal adenocarcinoma by binding miR-375 to target YAP1. 40) The activation of NF-κB1 signalling downregulates the expressions of miR-375 and miR-455, thereby upregulating the TRPV1 protein level leading to lumbar neuropathic pain. 41) Our study confirmed that the miR-375 inhibitor improved inflammation and oxidative stress in atherosclerosis by targeting GPR 39, but the factors regulating miR-375 were unknown, which is a limitation of this study and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…39) The amplification of AK4P1 may promote the development and progression of pancreatic ductal adenocarcinoma by binding miR-375 to target YAP1. 40) The activation of NF-κB1 signalling downregulates the expressions of miR-375 and miR-455, thereby upregulating the TRPV1 protein level leading to lumbar neuropathic pain. 41) Our study confirmed that the miR-375 inhibitor improved inflammation and oxidative stress in atherosclerosis by targeting GPR 39, but the factors regulating miR-375 were unknown, which is a limitation of this study and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…GTF2IP14 is classified as a pseudogene of GTF2I, which is a DNA sequence in the genome resembling a normal gene but not expressed. 23 Traditionally, pseudogenes were considered functionless. However, recent studies suggest that pseudogenes may play crucial roles in various diseases through true genes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other tumor-suppressive miRNAs, including miR-383, miR-375, miR-216b, miR-455, miR-202, and miR-494, were shown to be downregulated in the pancreatic cancer landscape. The underexpression or loss of expression of these miRNAs plays a substantial role in the progression of the disease by impacting multiple signaling pathways, such as AK4P1/SP1, c-MYC/SIRT1, the Wnt/β-catenin pathway, and the DLEU2/SMAD2 pathway, that lead to cancer cell proliferation, invasion, metabolism, and immune responses [53][54][55][56][57]. In the complex landscape of pancreatic cancer, these miRNAs bear promise as prognostic markers and potential targets for therapeutic intervention.…”
Section: Mirnas With Tumor-inhibitory Functionsmentioning
confidence: 99%